2006
DOI: 10.1093/molbev/msl026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic and Phylogenetic Analyses of Calcium ATPases and Calcium-Regulated Proteins in the Apicomplexa

Abstract: The phylum Apicomplexa comprises a large group of early branching eukaryotes that includes a number of human and animal parasites. Calcium controls a number of vital processes in apicomplexans including protein secretion, motility, and differentiation. Despite the importance of calcium as a second messenger, very little is known about the systems that control homeostasis or that regulate calcium signaling in parasites. The recent completion of many apicomplexan genomes provides new opportunity to define calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
154
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 85 publications
1
154
0
3
Order By: Relevance
“…In the Apicomplexa, Ca 2 þ acts as a secondary messenger via a range of calcium-dependent protein kinases, and initiates a number of signaling processes that are important for communication between eukaryotic cells (Nagamune and Sibley, 2006). Calcium signaling and calcium-regulated protein kinases have also been recognized for their critical role in establishing plant-microbe symbioses, especially in the plant-rhizobium system (Harper and Harmon, 2005;Oldroyd et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the Apicomplexa, Ca 2 þ acts as a secondary messenger via a range of calcium-dependent protein kinases, and initiates a number of signaling processes that are important for communication between eukaryotic cells (Nagamune and Sibley, 2006). Calcium signaling and calcium-regulated protein kinases have also been recognized for their critical role in establishing plant-microbe symbioses, especially in the plant-rhizobium system (Harper and Harmon, 2005;Oldroyd et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these data, the molecular characterization of IP 3 or ryanodine receptors in low eukaryotes is currently a challenge since the identification of orthologues has not been possible thus far, probably because of evolutionary sequence divergence (66). Traynor et al (96) identified an IP 3 receptor-like protein, IplA, in Dictyostelium discoideum, which possesses regions related to IP 3 R sequences, but thus far no evidence for IP 3 interaction exists.…”
Section: Camentioning
confidence: 99%
“…The biochemical pathways involved in host cell invasion have not been identified, but several lines of evidence suggest that Ca 2+ is important for parasite motility (Mondragon & Frixione, 1996;Smith, 1995;Werk, 1985;Pezella et al, 1997) and the Zhao et al, 1993). T. gondii contains more than 20 CDPK or CDPK-related kinases (Nagamune & Sibley, 2006). In the present, two related T. gondii CDPK isoforms have been recently identified, where TgCDPK1 seems to play a central role in regulating parasite motility and host cell invasion (Kieschnick et al, 2001).…”
Section: T He Apicomplexan Protozoan Toxoplasma Gondiimentioning
confidence: 92%